Technical Perspective: Narrowing the Semantic Gap In Distributed Programming. - Druschel, Peter (Communications of the ACM, 2009)
The author discusses advances made in computer science in declarative networking by researchers among multiple computer science specialties. Declarative networking includes ideas from the database, programming language, networking and distributed systems areas of computer science. In declarative networking, protocols are designed using high-level language which is compiled to executable code and deployed in a network.